A study of correlation of antenatal uterine scar thickness by transabdominal ultrasound with intraoperative lower uterine segment scar grading in elective repeat cesarean delivery - Vedantham, Haripriya; Nee Jahagirdar, Nandini Joshi; N., Ramadevi; Kamineni, Vasundhara; Saranu, Sarada (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Caesarean section (CS) is the most common obstetric surgery performed world-wide. The objective of this study was to correlate the antenatal sonographic lower uterine segment (LUS) scar thickness in women with previous one cesarean section with intra operative LUS scar grading. Methods: A Prospective observational study was conducted from December 2014 to November 2015. In a tertiary care center. 200 pregnant women from ANC clinic with previous one LSCS were recruited. Transabdominal USG done between 36-38 weeks. LUS thickness was measured from bladder wall-myometrium interphase and myometrium-chorioamniotic membrane inter phase. Intraoperative grading of LUS scar was done. Based on grading of scar participants were assigned into scar dehiscence group (grade III and IV LUS scar) and non-dehiscence group (Grade I and II LUS scar). Results: Mean LUS thickness was 3.41±0.623 mm (range: 2-7 mm). Mean LUS thickness in the scar dehiscence group and non-dehiscence group was 2.98±0.55 mm and 3.48±0.60 mm (P value < 0.05) respectively. A cut off value of 3.5 mm was derived from ROC with sensitivity, specificity, positive and negative predictive value of 92.6%, 54.3%, 24.0%, 97.8%, respectively. The present study reported 27 (13.5%) cases of scar dehiscence. Conclusions: Ultra-sonographic evaluation of LUS thickness correlated significantly with intraoperative LUS appearance. USG evaluation of LUS can be used as a screening test to predict the LUS scar integrity. Risk of dehiscence is increased in women with thin LUS i.e. sonographic LUS thickness of < 3.5 mm and needs to be further evaluated. Women with previous one LSCS with thick LUS i.e. sonographic LUS thickness of > 3.5 mm, can be counselled regarding TOLAC if not contraindicated.